Perceived Career Barriers Scale: Validation for a Lithuanian Sample - Sadauskaitė, Raimonda; Kairys, Antanas (Psichologija, 2021)
Career is undoubtedly an essential part of people’s lives. Unfortunately, career development does not necessarily go smoothly because various circumstances, such as career barriers, might constrain career development. Therefore, it is important to have valid and reliable instruments that help evaluate and understand this phenomenon. The current study aimed to test the validity of the Lithuanian version of the Perceived career barriers scale. The sample included 382 participants aged from 18 to 63 years (M = 37.5 years, SD = 13.6). Two hundred twenty-six of the participants were females, 155 were males, and one did not disclose their gender. The Perceived Career Barriers Scale was translated from the German language using the back translation technique. Its construct validity was confirmed by confirmatory factor analysis. Results also showed that the scale is reliable. Convergent validity of the scale was also confirmed – perceived career barriers correlated with career self-efficacy, Past Negative time perspective, Present Fatalistic time perspective, and Future Negative time perspective. The Perceived Career Barriers Scale may be used for further research, although it is recommended to conduct a more comprehensive validity evaluation.
Keywords: career barriers; scale validity